Pamidronic acid-grafted nHA/PLGA hybrid nanofiber scaffolds suppress osteoclastic cell viability and enhance osteoblastic cell activity. Issue 47 (14th November 2016) - Haider, Adnan; Versace, Davy-louis; Gupta, Kailash Chandra; Kang, Inn-Kyu
Abstract : Controlling osteoclast activity helps in prevention of bone resorption. Abstract : Osteoclasts have the capability to resorb bone. When osteoclastic activity is excessively high, bones generally become weakened and more prone to fracture. In order to treat excessive osteoclastic cell activity, maintain the balance between bone formation and resorption, and enhance osseointegration, pamidronic acid-grafted nanorod hydroxyapatite/poly(lactide- co -glycolide) (P- g -nHA/PLGA) scaffolds were fabricated via an electrospinning technique. Various spectroscopic techniques were used for the structural and morphological characterization of pristine PLGA, nHA/PLGA, and P- g -nHA/PLGA hybrid nanofiber scaffolds. The potential of the P- g -nHA/PLGA hybrid nanofiber scaffold as an implantable material was assessed through in vitro studies. The results showed that the viability of osteoclastic cells on the P- g -nHA/PLGA nanofiber scaffold was significantly suppressed due to the presence of pamidronic acid. Osteoblastic cells adhered and proliferated on all scaffolds tested; however, increased osteoblastic cell proliferation was observed on the P- g -nHA/PLGA hybrid and nHA/PLGA nanofiber scaffolds compared to the pristine PLGA nanofiber scaffolds. Therefore, these types of dual function P- g -nHA/PLGA hybrid nanofiber scaffolds could certainly be used in therapeutic bone implantation.